PORTFOLIO OPTIMIZATION USING A MICRO GENETIC ALGORITHM - Gutiérrez Urzúa, Mauricio (2007)
This research shows the portfolios optimization using micro genetic algorithms, to resolve the Markowitz's selecting investments model like a multi-objetive optimization, where is maximized profitalility and minization, where is maximized profitability and minimizing the risk, thus create a negotiation between the risk, thus create a negotiation between the two objectives, then find optimal solution. To solve this problem need a genetic algorithm for multi-objetive optimization, based Pareto's optimal. The results show that this application is more efficient than other similar processes(Non-dominated Sorting Genetic Algoritm II(NSGA II) and Pareto Archive Evolution Strategy (PAES)), but considering the period and the local market characteristics, its predictive power low.